Development and implementation of genomic predictions in beef cattle. (1st January 2016) - Berry, D.P.; Garcia, J.F.; Garrick, D.J.
Abstract: Beef production represents a considerable contribution to local and global economies and food security but also the environmental footprint of agricultural production systems. The development of accurate genomic evaluations in beef populations are more difficult than in dairy populations for reasons including the presence of multiple breeds, poor extent of phenotyping, lack of artificial insemination, and beef systems being generally a lower-margin business of poorer adopters of technology. Several options exist to minimize or overcome the limitations of developing accurate genomic evaluations for beef cattle.